The European reformations sourcebook - Lindberg, Carter (Blackwell Publ., 2000)
This collection of primary sources is designed to accompany Lindberg's The European Reformations text or any other text on the European Reformations. The sources included, selected from medieval and sixteenth-century texts comprise not only the major institutional and theological writings of the time but also popular expressions of religious and political grievances (Flugschriften, poems, satires, sermons) and women's writings. The collection is particularly notable for its comprehensive coverage and its inclusion of major portions of significant writings.Students and lecturers will find this volume useful because it brings together documents not easily accessible otherwise, as they are scattered through many collections of primary materials: also because it offers students their first direct engagement with the participants in the European Reformations. - Literaturverz. S. [282] - 285